Good stabilizer codes from quasi-cyclic codes over F4 and F9 - Ezerman, Martianus Frederic (2020)
We apply quantum Construction X on quasi-cyclic codes with large Hermitian hulls over F 4 and F 9 to derive good qubit and qutrit stabilizer codes, respectively. In several occasions we obtain quantum codes with stricly improved parameters than the current record. In numerous other occasions we obtain quantum codes with best-known performance. For the qutrit ones we supply a systematic construction to fill some gaps in the literature.